The gas-phase infrared spectra of the 2-methylallyl radical and its high-temperature reaction products. Issue 13 (18th March 2022) - Preitschopf, Tobias; Hirsch, Florian; Lemmens, Alexander K.; Rijs, Anouk M.; Fischer, Ingo
Abstract : The resonance-stabilized 2-methylallyl radical, 2-MA, is considered as a possible intermediate in the formation of polycyclic aromatic hydrocarbons (PAHs) in combustion processes. Abstract : The resonance-stabilized 2-methylallyl radical, 2-MA, is considered as a possible intermediate in the formation of polycyclic aromatic hydrocarbons (PAHs) in combustion processes. In this work, we report on its contribution to molecular growth in a high-temperature microreactor and provide mass-selective IR/UV ion dip spectra of the radical, as well as the various jet-cooled reaction products, employing free electron laser radiation in the mid-infrared region. Small (aromatic) hydrocarbons such as fulvene, benzene, styrene, or para -xylene, as well as polycyclic molecules, like (methylated) naphthalene, were identified with the aid of ab initio DFT computations. Several reaction products differ by one or more methyl groups, suggesting that molecular growth is dominated by (de)methylation in the reactor.